Heavy Metal Contamination of the River Nile Environment, Rosetta Branch, Egypt - Al-Afify, Afify D. G.; Abdel-Satar, Amaal M. (Water, air, and soil pollution, 2022)
The Rosetta Branch is one of Egypt’s most important Nile River branches, providing freshwater to multiple cities. However, its water quality has been deteriorating, with various wastes containing high loads of heavy metals being discharged into its body of water. Seasonally, water and sediment samples and two native aquatic plants ( Ceratophyllum demersum and Eichhornia crassipes ) were collected and analyzed from the Rosetta Branch to assess the level of metal contamination (Fe, Mn, Zn, Cu, Pb, Ni, Cd, Cr, and Co) using different metal indices. The levels of some metals in the branch water overstepped those suitable for drinking water and aquatic life. In increasing order, the means of the heavy metal concentrations in branch water (µg/L) were Cd (1.8–4.9) < Co (7.18–28.1) ≈ Ni (9.0–25.1) < Cr (8.56–27.4) < Cu (14–75) < Pb (9.3–67.9) < Zn (22–133) < Mn (68–220) < Fe (396–1640). All the metal indices measured in the sediment confirmed the Ni and Cd contamination, where Ni and Cd in the sediment surpass the sediment quality guidelines in 80% and 53% of samples, respectively, reflecting frequent adverse effects on aquatic organisms. According to the bioconcentration factor, C. demersum and E. crassipes have higher accumulation capacities mainly for Cd than those for other metals considered as major pollutants in the water and sediment of Rosetta Branch, reflecting the role of hydrophytes in the biological treatment of polluted water in aquatic environments.